A Site-Specific Genetic Modification for Induction of Pluripotency and Subsequent Isolation of Derived Lung Alveolar Epithelial Type II Cells. (13th January 2014) - Yan, Qing; Quan, Yuan; Sun, Huanhuan; Peng, Xinmiao; Zou, Zhengyun; Alcorn, Joseph L.; Wetsel, Rick A.; Wang, Dachun
Abstract : Human induced pluripotent stem cells (hiPSCs) have great therapeutic potential in repairing defective lung alveoli. However, genetic abnormalities caused by vector integrations and low efficiency in generating hiPSCs, as well as difficulty in obtaining transplantable hiPSC-derived cell types are still major obstacles. Here we report a novel strategy using a single nonviral site-specific targeting vector with a combination of Tet-On inducible gene expression system, Cre/ lox P switching gene expression system, and alveolar epithelial type II cell (ATIIC)-specific Neomycin R transgene expression system. With this strategy, a single copy of all of the required transgenes can be specifically knocked into a site immediately downstream of β-2-microglobulin (B2M) gene locus at a high frequency, without causing B2M dysfunction. Thus, the expression of reprogramming factors, Oct4, Sox2, cMyc, and Klf4, can be precisely regulated for efficient reprogramming of somatic cells into random integration-free or genetic mutation-free hiPSCs. The exogenous reprogramming factor transgenes can be subsequently removed after reprogramming by transient expression of Cre recombinase, and the resulting random integration-free and exogenous reprogramming factor-free hiPSCs can be selectively differentiated into a homogenous population of ATIICs. In addition, we show that these hiPSC-derived ATIICs exhibit ultrastructural characteristics and biological functions of normal ATIICs. When transplanted into bleomycin-challenged mice lungs, hiPSC-derived ATIICs efficiently remain and re-epithelialize injured alveoli to restore pulmonary function, preventing lung fibrosis and increasing survival without tumorigenic side effect. This strategy allows for the first time efficient generation of patient-specific ATIICs for possible future clinical applications. Stem Cells 2014;32:402–413